TEACHING BALAGHAH AESTHETICS: PEDAGOGICAL NEGOTIATION OF MEANING IN TASYBIH AND MAJAZ AT ISLAMIC BOARDING SCHOOL - Ekawati Ekawati; Untung Famuji; Irhamil Muthoharoh; Wilnan Fatahillah; Fathalla Mohamed Fathalla Zekaizak (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
This study aimed to examine how educators teach the aesthetic concepts of Majaz (figurative language) and Tasybih (simile) through a process of negotiation of meaning. This qualitative research using a case study approach aims to analyze the pedagogical dynamics and learning trajectories of Balaghah at the Attaqwa Putra Islamic Boarding School. Data were collected through participatory classroom observation, in-depth interviews with teachers and students, and documentation of teaching materials and Pegon annotations. The results of the study had shown three main findings that are integrated into the Arabic rhetoric learning process. First, the selection and curation of teaching materials are carried out strategically through socio-cultural reconceptualization to bridge the gap between classical texts and the context of the lives of modern students. Second, the implementation of a layered learning strategy that combines inductive, deductive, analytical, and applicative approaches successfully facilitates the negotiation of meaning through scaffolding techniques and dialogic pauses. Third, the use of Socratic questioning techniques has been proven to accelerate the trajectory of students' cognitive maturity while fostering aesthetic sensitivity (dzauq) and intellectual satisfaction. The implications of this research confirm that the modernization of Arabic language learning in Islamic boarding schools does not have to eliminate local traditions such as sorogan and bandongan, but can be optimized as a pedagogical innovation based on Higher-Order Thinking Skills (HOTS) that fortifies students from textual literalism and supports the formation of a moderate religious character (Wasathiyyah).